Cervical cancer with patent foramen ovale metastasis to the left ventricle: a case report - Lanyue Huang; Yanhui Li; Rui Li; Houjuan Zuo; Daowen Wang; Hesong Zeng; Peng Deng; Ligang Liu; Xiang Wei; Jingqun Zhang (World Journal of Surgical Oncology)
Abstract Background Metastasis of malignant tumors to the cardiac endocardium is rare and mainly involves the right side of the heart. It is extremely rare to involve the left cardiac endocardium, especially when there is neither pulmonary metastasis nor primary lung cancer, which we call “isolated” left cardiac endocardium metastasis in this paper. Few such cases previously reported in the literature were not screened for patent foramen ovale (PFO). Case presentation This article reports a case of a young woman with a history of surgery for cervical cancer, who was transferred to our hospital with a suspected diagnosis of PFO after recent recurrent multiple cerebral infarctions. On admission, transthoracic echocardiography revealed multiple stringy vegetations in the left ventricle, which were subsequently removed surgically, with intraoperative confirmation of a patent foramen ovale and closure of it simultaneously. According to her medical history and pathological results, she was diagnosed with left ventricular metastasis of cervical cancer, a rare case of isolated left heart endocardium metastasis without previous pulmonary metastasis, presumably through the patent foramen ovale. Conclusion PFO may play an important role in the process of isolated left heart endocardium metastasis in patients with distant malignancies and paradoxical embolism. Screening for PFO in high-risk patients may have significant clinical significance.